Traitement Chirurgical Des Eventrations Abdominales Avec Pose De Prothese: Experience A Court Terme Du Chu Yalgado Ouedraogo - Zaré Cyprien; Traoré Sékou; Ouangré Edgard; Belemlilga Hermann; Zida Maurice; Traoré Alain Ibrahim (European Scientific Journal, ESJ, 2017)
Title: Surgical management of abdominal incisional hernia with mesh placement: short- term experience of the University Hospital Yalgado Ouedraogo Introduction: The incisional hernia repair has several variants depending on the implantation site of the mesh. It may be intraperitoneal, preperitoneal, pre-mucosal or pre-musculoskeletal. Objective: The aim of the work was to report at short term the experience of the general and digestive surgery service of the Yalgado Ouédraogo University Hospital Center for the surgical management of abdominal incisional hernia with mesh placement in retro-muscular prefascial Patients and methods: This was a cross-sectional and descriptive study with a review of the files and a survey of 17 patients operated on for voluminous abdominal incisional hernia (diameter greater than 10 cm) from September 1, 2014 to August 31, 2015. Results: The mean duration of hospitalization was 7 days with extremes of 4 and 15 days. The dressings lasted on average 7 days with extremes of 4 and 15 days. The suction drains remained in place on average 8.56 days with extremes of 5 and 14 days and the mean duration of the abdominal wall contusion was 24.5 days with extremes of 10 and 40 days. The early postoperative complications were minor: 8 seromas, 1 hematomas, 1 superficial infection of the wall. Patients were followed for an average duration of 9.47 months with extremes of 4 and 14 months. The complications during this period were: 3 minor residual pain (limited to the scar) and 1 recurrence. Thirteen patients (76.5%) were satisfied with the intervention. Mortality was zero. Conclusion: Short time complications related to the surgical management of abdominal incisional hernia with mesh placement in retro-muscular prefascial in CHUYO are mainly minor.